Modified polyesters, processes for their preparation and use

CN122978657APending Publication Date: 2026-10-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510532618.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

共聚改性的原理主要是在合成过程中,引入柔性链段、不对称结构和极性基团等改性组分使聚酯改性,但往往造成聚酯本身力学性能如拉伸强度的大幅下降,且聚酯的抗静电性能提高有限

Benefits of technology

[0015]通过上述技术方案,本发明提供的改性聚酯中同时含有碳化硅纳米片和共聚酯,所述共聚酯含有由改性单体形成的结构单元A和具有醚基的结构单元B,改性单体选自结构如式(I)所示的改性单体a、结构如式(II)所示的改性单体b、式(III)所示的改性单体c、式(IV)所示的改性单体d和式(V)所示的改性单体e中的至少一种,并对碳化硅纳米片和结构单元B的含量进行限定。通过结构单元A和特定含量的碳化硅纳米片以及结构单元B之间的相互作用,能够在保证力学性能的同时有效提高聚酯的抗静电性能,同时也能够有效保证聚酯的导热性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978657A_ABST
    Figure CN122978657A_ABST
Patent Text Reader

Abstract

The present application relates to polyester modification, discloses a modified polyester and its preparation method and application. The modified polyester contains silicon carbide nanosheet and copolyester, the copolyester contains structural unit A formed by modified monomer and structural unit B with ether group, the modified monomer is selected from at least one of modified monomer a with structure as shown in formula (I), modified monomer b with structure as shown in formula (II), modified monomer c shown in formula (III), modified monomer d shown in formula (IV) and modified monomer e shown in formula (V), R4, R5, R6, R 13 , R 14 and R 15 Each independently is hydrogen or C1-C3 alkyl, R7 and R8 each independently is hydrogen or hydroxyl-substituted alkyl, R9, R 10 and R 11 Each independently is C1-C4 alkylene, R 12 , R1, R2 and R3 each independently is C4-C10 alkylene. The modified polyester has good antistatic property, and also has higher tensile strength and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polyester modification, specifically to a modified polyester, its preparation method, and its applications. Background Technology

[0002] PET polyester, as an important engineering plastic, has wide applications in packaging, films, fibers, and other fields. Meanwhile, with technological advancements and market expansion, the performance requirements for PET polyester materials are increasingly stringent. Particularly in high-cleanliness environments, electronic device packaging, and food packaging, strict requirements are placed on the antistatic properties of the materials. However, due to its structure, PET polyester inherently has insufficient antistatic properties, often leading to static electricity accumulation and dust attraction during application, which not only affects product quality but may also pose safety hazards. Therefore, improving the antistatic properties of PET polyester has significant practical importance and application value, not only meeting market demands but also further expanding its application areas.

[0003] There are three main methods to improve the antistatic properties of PET polyester: surface treatment, blending, and copolymerization. Compared to the first two methods, copolymerization modification can produce copolyesters with smooth surfaces and durable antistatic properties. The principle of copolymerization modification is mainly to introduce modifying components such as flexible segments, asymmetric structures, and polar groups during the synthesis process to modify the polyester. However, this often leads to a significant decrease in the mechanical properties of the polyester itself, such as tensile strength, and the improvement in the antistatic properties of the polyester is limited. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems of significantly reduced mechanical properties and limited improvement in antistatic properties of polyesters prepared by copolymer modification in the prior art. This invention provides a modified polyester, its preparation method, and its application. The modified polyester has good antistatic properties while ensuring mechanical properties, and also has high thermal conductivity.

[0005] To achieve the above objectives, a first aspect of the present invention provides a modified polyester comprising silicon carbide nanosheets and a copolyester, wherein the copolyester comprises a structural unit A formed by a modified monomer and a structural unit B having an ether group, wherein the modified monomer is selected from at least one of modified monomer a with a structure as shown in formula (I), modified monomer b with a structure as shown in formula (II), modified monomer c with a structure as shown in formula (III), modified monomer d with a structure as shown in formula (IV), and modified monomer e with a structure as shown in formula (V), wherein the content of the silicon carbide nanosheets in the modified polyester is 0.25-1 wt%, and the content of the structural unit B is 0.1-15 wt%.

[0006]

[0007] Among them, R4, R5, R6, R13 R 14 and R 15 Each is independently hydrogen or C1-C3 alkyl, R7 and R8 are independently hydrogen- or hydroxyl-substituted alkyl groups, R9, R 10 and R 11 Each is independently a C1-C4 alkylene group, R 12 R1, R2 and R3 are each independently C4-C10 alkylene groups, and p and q are each independently natural numbers from 3 to 300.

[0008] A second aspect of the present invention provides a method for preparing a modified polyester, the method comprising the following steps:

[0009] S1. Under the conditions of esterification reaction, the diacid monomer, diol monomer, modified monomer and catalyst are subjected to the first stage reaction to obtain the prepolymer.

[0010] S2. Under the conditions of polymerization reaction, the prepolymer, silicon carbide nanosheets and the compound containing ether groups are subjected to a second-stage reaction;

[0011] The modified monomer is selected from at least one of modified monomer a with the structure shown in formula (I), modified monomer b with the structure shown in formula (II), modified monomer c with the structure shown in formula (III), modified monomer d with the structure shown in formula (IV), and modified monomer e with the structure shown in formula (V). The amount of silicon carbide nanosheets is 0.25-1 wt% based on the theoretical yield of the modified polyester, and the amount of the compound containing the ether group is 0.1-15 wt%.

[0012]

[0013] Among them, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen or C1-C3 alkyl, R7 and R8 are independently hydrogen- or hydroxyl-substituted alkyl groups, R9, R 10 and R 11 Each is independently a C1-C4 alkylene group, R 12 R1, R2 and R3 are each independently C4-C10 alkylene groups, and p and q are each independently natural numbers from 3 to 300.

[0014] A third aspect of the present invention provides the application of the above-described modified polyester in packaging, textile or electronic materials.

[0015] Through the above technical solution, the modified polyester provided by the present invention simultaneously contains silicon carbide nanosheets and a copolyester. The copolyester contains structural unit A formed by a modified monomer and structural unit B having an ether group. The modified monomer is selected from at least one of modified monomer a (as shown in formula (I), modified monomer b (as shown in formula (II), modified monomer c (as shown in formula (III), modified monomer d (as shown in formula (IV), and modified monomer e (as shown in formula (V)). The content of silicon carbide nanosheets and structural unit B is limited. Through the interaction between structural unit A, a specific amount of silicon carbide nanosheets, and structural unit B, the antistatic properties of the polyester can be effectively improved while ensuring mechanical properties, and the thermal conductivity of the polyester can also be effectively guaranteed. Attached Figure Description

[0016] Figure 1 This is a flow chart of copolyester polymerization. Detailed Implementation

[0017] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0018] As previously stated, a first aspect of the present invention provides a modified polyester comprising silicon carbide nanosheets and a copolyester, wherein the copolyester comprises a structural unit A formed by a modified monomer and a structural unit B having an ether group, wherein the modified monomer is selected from at least one of modified monomer a with a structure as shown in formula (I), modified monomer b with a structure as shown in formula (II), modified monomer c with a structure as shown in formula (III), modified monomer d with a structure as shown in formula (IV), and modified monomer e with a structure as shown in formula (V), wherein the content of the silicon carbide nanosheets in the modified polyester is 0.25-1 wt%, and the content of the structural unit B is 0.1-15 wt%.

[0019]

[0020] Among them, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen or C1-C3 alkyl, R7 and R8 are independently hydrogen- or hydroxyl-substituted alkyl groups, R9, R 10 and R 11 Each is independently a C1-C4 alkylene group, R 12R1, R2 and R3 are each independently C4-C10 alkylene groups, and p and q are each independently natural numbers from 3 to 300.

[0021] According to the present invention, the above-mentioned structural units can be determined by infrared spectroscopy, mass spectrometry, etc.

[0022] During their research, the inventors discovered that the modified polyester simultaneously contains silicon carbide nanosheets, structural unit A formed by modified monomers, and structural unit B with ether groups. The modified monomers are selected from at least one of the following: modified monomer a (structure shown in formula (I), modified monomer b (structure shown in formula (II), modified monomer c (structure shown in formula (III), modified monomer d (structure shown in formula (IV), and modified monomer e (structure shown in formula (V))). The content of silicon carbide nanosheets and structural unit B is also limited. Through the interaction between structural unit A, a specific amount of silicon carbide nanosheets, and structural unit B, the antistatic properties of the polyester can be effectively improved while ensuring mechanical properties, and the thermal conductivity of the polyester can also be effectively guaranteed.

[0023] According to the present invention, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen, methyl, ethyl, or propyl. R7 and R8 are independently hydrogen or alkyl groups with substituted hydroxyl groups, and R9 and R... 10 and R 11 Each is independently methylene, ethylene, propylene, or butylene, R 12 R1, R2, and R3 are each independently butylene, pentylene, hexylene, heptylene, octylene, nonylene, or decylene. In the modified polyester, the content of the silicon carbide nanosheets can be 0.25 wt%, 0.4 wt%, 0.55 wt%, 0.7 wt%, 0.85 wt%, 1 wt%, or any value within a range formed by any two of these values. The content of structural unit B can be 0.1 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, or any value within a range formed by any two of these values.

[0024] Preferably, R7 and R8 are each independently a hydroxyl-substituted C1-C4 alkyl group, more preferably a hydroxyl-substituted C2-C3 alkyl group. The structural units A and B having the above structure, as well as the silicon carbide nanosheets, exhibit better interaction effects, thereby further improving the antistatic and tensile properties of the polyester. Further preferably, R4, R5, R6, and R8 are hydroxyl-substituted C1-C4 alkyl groups, and more preferably R7, R8, R9, R1, R1, R2, R1, R3, R1, R4, R5, R6, R9, R9, R1, R9, R1, R9, R1, R9, R1, R1, R9, R1, R1, R1, R2 ...13 R 14 and R 15 Each is independently hydrogen, R9, R 10 and R 11 Each is independently a C2-C3 alkylene group.

[0025] R7 and R8 can be the same or different, R9, R 10 and R 11 They can be the same or different. Preferably, R7 and R8 are the same, and R9 and R... 10 and R 11 Same. More preferably, R9, R 10 and R 11 It is ethylene.

[0026] Preferably, the modified monomer is selected from at least one of modified monomer a, modified monomer c, modified monomer d, and modified monomer e. During the research, it was found that the structural units A and B formed by the above-mentioned modified monomers, and the silicon carbide nanosheets, have better interaction effects, thereby further improving the antistatic and tensile properties of the polyester. Considering the ability to further improve the antistatic and tensile properties of the polyester, it is further preferred that the modified monomer is modified monomer a and modified monomer e.

[0027] Preferably, the mass ratio of modified monomer a to modified monomer e is 1:1.2-2. Controlling the mass ratio of modified monomer a to modified monomer e within the above range can further improve the antistatic and tensile properties of the polyester. Further preferably, considering the ability to further improve the antistatic and tensile properties of the polyester, the mass ratio of modified monomer a to modified monomer e is 1:1.5-1.8.

[0028] Preferably, the structure of structural unit B is as shown in equation (VI) or equation (VII).

[0029]

[0030] Among them, R 15 and R 16 Each is independently a C1-C4 alkylene group, R 17 The alkyl group is C1-C4, and m and n are each independent natural numbers between 9 and 140, preferably between 20 and 50. Studies have found that structural unit B with the above structure has better interaction with structural unit A and silicon carbide nanosheets, thereby further improving the antistatic properties, tensile properties, and thermal conductivity of the polyester. From the perspective of further improving the tensile properties of the polyester, it is further preferred that the structure of structural unit B is as shown in formula (VI).

[0031] According to the present invention, R 15 and R 16 Each can be independently methylene, ethylene, propylene, or butylene. 17 It can be methyl, ethyl, propyl or butyl, and m and n can each independently be 9, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, or any value between these values.

[0032] Preferably, R 15 and R 16 Each is independently a C2-C3 alkylene group, R 17 It is a C1-C2 alkyl group. The structural units A and B of the above structure have a better interaction effect with the silicon carbide nanosheets, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of the polyester. Further preferably, considering the ability to further improve the antistatic properties, tensile strength, and thermal conductivity of the polyester, R... 15 and R 16 Each is independently ethylene, R 17 It is a methyl group.

[0033] Preferably, the modified monomer is selected from at least one of diethyl isophthalate sulfonate (SIPE), 5-isophthalate sulfonate, tris(hydroxyethyl) isocyanurate, nylon 6, 2-hydroxyisobutyric acid and 10-hydroxydecanoic acid.

[0034] Preferably, in the modified polyester, the content of structural unit A is 10-30 wt%, which can be 10 wt%, 14 wt%, 18 wt%, 22 wt%, 26 wt%, 30 wt%, or any value within the range formed by these values. Studies have found that silicon carbide nanosheets, structural unit A, and structural unit B at the above-mentioned contents have better interaction effects, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of the polyester. Further preferably, considering the ability to further improve the antistatic properties, tensile strength, and thermal conductivity of the polyester, the mass ratio of the silicon carbide nanosheets, structural unit A, and structural unit B is 1:10-40:1-12. More preferably, the mass ratio of structural unit A to structural unit B is 1:0.1-1.5.

[0035] According to the present invention, the content of silicon carbide can be determined by inductively coupled plasma (ICP) testing, and the content of structural units A and B can be determined by nuclear magnetic resonance hydrogen spectroscopy testing.

[0036] Preferably, the silicon carbide nanosheets have a length of 0.5-1.3 μm and a width of 1-6 nm. Studies have found that limiting the size of the silicon carbide nanosheets to the above range can further improve the interaction between them and structural unit A and structural unit B, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of the polyester.

[0037] Preferably, the modified polyester further contains structural unit C as shown in formula (VIII) and structural unit D as shown in formula (IX).

[0038] -OR B -O- formula (IX),

[0039] Among them, R A It is a C1-C4 alkyl group, R B It is a C2-C4 alkylene group, and p is a natural number between 0 and 4. The modified monomers C and D, A and B, and silicon carbide nanosheets have better interaction effects, resulting in modified polyesters with better antistatic properties, tensile strength, and thermal conductivity.

[0040] Preferably, the modified polyester also contains antimony. Studies have found that the presence of antimony in the modified polyester enhances the interaction between the silicon carbide nanosheets, modified monomer A, modified monomer B, modified monomer C, and structural unit D, thereby further improving the antistatic and tensile properties of the polyester. Further preferably, considering the potential for further improvement in the antistatic and tensile properties of the polyester, the antimony content in the modified polyester is 125-165 ppm.

[0041] Preferably, the surface resistivity of the modified polyester is 6 × 10⁻⁶. 8 -2×10 12 Ω, tensile strength of 40-60 MPa, thermal conductivity of 0.17-0.28 W·m -1 ·K -1 .

[0042] According to the present invention, surface resistivity is measured using a high-resistivity meter, and the test conditions are in accordance with GB / T33398-2016; after injection molding, the slices are vacuum dried at room temperature for 24 hours and then the tensile strength is tested, and the test standard is in accordance with GB 1040-2006; thermal conductivity is measured using a thermal conductivity meter, using the line cross method, at a test temperature of 25℃, with a measurement range of ≤2W / (m·K), and a test voltage of 1V, and the result is the average of 5 tests.

[0043] Preferably, the intrinsic viscosity of the modified polyester is 0.6-0.7 dL / g.

[0044] According to the present invention, the intrinsic viscosity was tested using a Y501 C relative viscometer, the solvent was phenol / tetrachloroethane (mass ratio 3:2), the test temperature was (25±0.1)℃, and the relevant test standards were performed in accordance with GB / T 14190-2017 "Test Method for Fiber Grade Polyester (PET) Chips".

[0045] A second aspect of the present invention provides a method for preparing a modified polyester, the method comprising the following steps:

[0046] S1. Under the conditions of esterification reaction, the diacid monomer, diol monomer, modified monomer and catalyst are subjected to the first stage reaction to obtain the prepolymer.

[0047] S2. Under the conditions of polymerization reaction, the prepolymer, silicon carbide nanosheets and the compound containing ether groups are subjected to a second-stage reaction;

[0048] The modified monomer is selected from at least one of modified monomer a with the structure shown in formula (I), modified monomer b with the structure shown in formula (II), modified monomer c with the structure shown in formula (III), modified monomer d with the structure shown in formula (IV), and modified monomer e with the structure shown in formula (V). The amount of silicon carbide nanosheets is 0.25-1 wt% based on the theoretical yield of the modified polyester, and the amount of the compound containing the ether group is 0.1-15 wt%.

[0049]

[0050] Among them, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen or C1-C3 alkyl, R7 and R8 are independently hydrogen- or hydroxyl-substituted alkyl groups, R9, R 10 and R 11 Each is independently a C1-C4 alkylene group, R 12 R1, R2 and R3 are each independently C4-C10 alkylene groups, and p and q are each independently natural numbers from 3 to 300.

[0051] During the research process, the inventors discovered that the modified polyester prepared by the above method has good antistatic properties while ensuring tensile properties.

[0052] Preferably, R7 and R8 are each independently a hydroxyl-substituted C1-C4 alkyl group, more preferably a hydroxyl-substituted C2-C3 alkyl group. The modified monomer having the above structure exhibits better interaction with the ether-containing compound and the silicon carbide nanosheets, thereby further improving the antistatic properties, tensile properties, and thermal conductivity of the polyester. Further preferably, considering the ability to further improve the antistatic properties, tensile properties, and thermal conductivity of the polyester, R4, R5, R6, and R8 are... 13 R 14 and R 15 Each is independently hydrogen, R9, R 10 and R 11 Each is independently a C2-C3 alkylene group.

[0053] R7 and R8 can be the same or different, R9, R 10 and R 11 They can be the same or different. Preferably, R7 and R8 are the same, and R9 and R... 10 and R 11 Same. More preferably, R9, R 10 and R 11 It is ethylene.

[0054] Preferably, the modified monomer is selected from at least one of diethyl isophthalate sulfonate (SIPE), 5-isophthalate sulfonate, tris(hydroxyethyl) isocyanurate, nylon 6, 2-hydroxyisobutyric acid and 10-hydroxydecanoic acid.

[0055] Preferably, the modified monomer is selected from at least one of modified monomer a, modified monomer c, modified monomer d, and modified monomer e. During the research process, it was found that the above-mentioned modified monomers have better interaction effects with compounds containing ether groups and silicon carbide nanosheets, thereby further improving the antistatic properties, tensile properties, and thermal conductivity of the polyester. Considering the ability to further improve the antistatic properties, tensile properties, and thermal conductivity of the polyester, it is further preferred that the modified monomers are modified monomer a and modified monomer e.

[0056] Preferably, the mass ratio of modified monomer a to modified monomer e is 1:1.2-2. Controlling the mass ratio of modified monomer a to modified monomer e within the above range can further improve the antistatic and tensile properties of the polyester. Further preferably, considering the ability to further improve the antistatic and tensile properties of the polyester, the mass ratio of modified monomer a to modified monomer e is 1:1.5-1.8.

[0057] Preferably, the ether-containing compound has a structure as shown in formula (VI) or formula (VII).

[0058]

[0059] Among them, R 15 and R 16 Each is independently a C1-C4 alkylene group, R 17 The alkyl group is C1-C4, and m and n are each independently natural numbers between 9 and 140, preferably between 20 and 50. Studies have found that compounds with the above structure have better interaction effects with modified monomers and silicon carbide nanosheets, thereby further improving the antistatic properties, tensile properties, and thermal conductivity of polyesters. Further preferably, considering the ability to further improve the antistatic properties, tensile properties, and thermal conductivity of polyesters, the ether-containing compound has the structure shown in formula (VI).

[0060] Preferably, R 15 and R 16 Each is independently a C2-C3 alkylene group, R 17 It is a C1-C2 alkyl group. The compounds and modified monomers with the above structure have better interaction effects with silicon carbide nanosheets, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of the polyester. Further preferably, R... 15 and R 16 Each is independently ethylene, R 17 It is a methyl group.

[0061] Preferably, the amount of the modified monomer is 10-30 wt%, based on the theoretical yield of the modified polyester. Studies have found that the silicon carbide nanosheets, the ether-containing compound, and the modified monomer at the above-mentioned amounts have a better interaction effect, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of the polyester. Further preferably, considering the ability to further improve the antistatic properties, tensile strength, and thermal conductivity of the polyester, the ratio of the silicon carbide nanosheets, the ether-containing compound, and the modified monomer is 1:10-40:1-12. More preferably, the ratio of the ether-containing compound to the modified monomer is 1:0.1-1.5.

[0062] Preferably, the silicon carbide nanosheets have a length of 0.6-1.2 μm and a width of 2-6 nm. Studies have found that limiting the size of the silicon carbide nanosheets to the above range can further enhance their interaction with compounds containing ether groups and modified monomers, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of polyester.

[0063] Preferably, the dicarboxylic acid monomer has the structure shown in formula (VIII), and the diol monomer has the structure shown in formula (IX).

[0064] -OR B -O- formula (IX),

[0065] Among them, R A It is a C1-C4 alkyl group, R B It is a C2-C4 alkylene group, and p is a natural number between 0 and 4. In the above system, there is a better interaction between the modified monomer, the ether-containing compound, and the silicon carbide nanosheets, which can further improve the antistatic properties, tensile strength, and thermal conductivity of the modified polyester.

[0066] Preferably, the catalyst is an antimony-based catalyst. Antimony-based catalysts exhibit better reaction performance, thereby further improving the antistatic properties, tensile strength, and thermal conductivity of the modified polyester. More preferably, the antimony-based catalyst is selected from at least one of antimony oxide, antimony acetate, and antimony glycolate. Considering the potential for further improvement in the antistatic properties, tensile strength, and thermal conductivity of the polyester, it is further preferably that the amount of the antimony-based catalyst, calculated as antimony, is 125-165 ppm based on the theoretical yield of the modified polyester.

[0067] Preferably, the esterification reaction conditions include at least the following: a temperature of 235-255°C, which can be 235°C, 240°C, 245°C, 250°C, 255°C, or any value within this range; and a time of 90-120 min, which can be 90 min, 95 min, 100 min, 105 min, 110 min, 115 min, 120 min, or any value within this range. The method further includes pre-polymerizing the prepolymer under a vacuum of less than 150 Pa for 30-60 min before the second-stage reaction. Under these conditions, the reaction effect is better, thereby further improving the antistatic properties and tensile strength of the subsequently obtained polyester.

[0068] Preferably, the conditions for the polycondensation reaction include at least a temperature of 270-280°C, which can be 270°C, 272°C, 274°C, 276°C, 278°C, 280°C, or any value within a range of these temperatures. Better polycondensation effects are achieved under these conditions.

[0069] A third aspect of the present invention provides the application of the above-described modified polyester in packaging, textile or electronic materials.

[0070] The present invention will be described in detail below through embodiments. In the following embodiments, surface resistivity was measured using a high-resistivity meter, and the test conditions were performed according to GB / T 33398-2016; after injection molding, the slices were vacuum dried at room temperature for 24 hours and then the tensile strength was tested according to GB 1040-2006; thermal conductivity was measured using a thermal conductivity meter, employing the line cross method, at a test temperature of 25℃, with a measurement range ≤2W / (m·K), and a test voltage of 1V, and the result was the average of 5 tests. The silicon carbide nanosheet-1 has a lateral length of 0.8±0.1μm and a longitudinal thickness of 4±1nm; the silicon carbide nanosheet-2 has a lateral length of 0.6±0.1μm and a longitudinal thickness of 2±1nm; the silicon carbide nanosheet-3 has a lateral length of 1.2±0.1μm and a longitudinal thickness of 6±1nm; all the above nanosheets were provided by Henan Pingdingshan Yicheng New Material Co., Ltd. The silicon carbide nanospheres, with a particle size of 450 nm, were provided by Hebei Xingrongyuan Metal Materials Co., Ltd.; Nylon 6, with a molecular weight of 3000 and a molecular weight distribution of 1.56, was purchased from Guangzhou Hengshenmeida New Materials Co., Ltd.; PEG, with a molecular weight of 2000 and a molecular weight distribution of 1.05, was purchased from Shanghai Dongda Chemical Co., Ltd.; and polyethylene glycol monomethyl ether, with a molecular weight of 2000 and a molecular weight distribution of 1.10, was purchased from Taizhou Jiayin Chemical Co., Ltd.

[0071] Example 1

[0072] Terephthalic acid, ethylene glycol, SIPE, and antimony oxide were added to a 20L polymerization reactor. The molar ratio of terephthalic acid to ethylene glycol was 1:1.6. The amount of SIPE added accounted for 10 wt% of the theoretical polyester yield, and the amount of antimony oxide added (calculated as antimony) accounted for 145 ppm of the theoretical polyester yield. After the addition was complete, the reactor was purged with nitrogen three times, and the temperature was raised to 245℃. The esterification reaction was carried out at atmospheric pressure for 100 min. After the reaction, 3 wt% of PEG and 0.25 wt% of silicon carbide nanosheets-1 (based on the theoretical polyester yield) were added. After stirring for 15 min, pre-polymerization was carried out under low vacuum for 45 min. The vacuum was then further reduced to below 100 Pa, and the polycondensation reaction was carried out at 275℃. After the reaction was completed, the product was extruded by a melt pump, pelletized, and dried. The preparation flow chart is shown below. Figure 1 .

[0073] Example 2

[0074] The modified polyester was prepared according to the method of Example 1, except that the amount of silicon carbide nanosheets-1 used was 0.5 wt% of the theoretical yield of polyester.

[0075] Example 3

[0076] The modified polyester was prepared according to the method of Example 1, except that the amount of silicon carbide nanosheets-1 used was 0.75 wt% of the theoretical yield of polyester.

[0077] Example 4

[0078] The modified polyester was prepared according to the method of Example 1, except that the amount of silicon carbide nanosheets-1 used was 1 wt% of the theoretical yield of polyester.

[0079] Example 5

[0080] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 1 wt%.

[0081] Example 6

[0082] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 1.5 wt%.

[0083] Example 7

[0084] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 2 wt%.

[0085] Example 8

[0086] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 2.5 wt%.

[0087] Example 9

[0088] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 5 wt%.

[0089] Example 10

[0090] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 10 wt%.

[0091] Example 11

[0092] The modified polyester was prepared according to the method of Example 3, except that the amount of PEG used was 15 wt%.

[0093] Example 12

[0094] The modified polyester was prepared according to the method of Example 9, except that SIPE was replaced with nylon 6.

[0095] Example 13

[0096] The modified polyester was prepared according to the method of Example 12, except that the amount of nylon 6 used was 30 wt%.

[0097] Example 14

[0098] The modified polyester was prepared according to the method of Example 9, except that SIPE was replaced with 2-hydroxyisobutyric acid.

[0099] Example 15

[0100] The modified polyester was prepared according to the method of Example 14, except that the amount of 2-hydroxyisobutyric acid used was 30 wt%.

[0101] Example 16

[0102] The modified polyester was prepared according to the method of Example 9, except that PEG was replaced with polyethylene glycol monomethyl ether.

[0103] Example 17

[0104] The modified polyester was prepared according to the method of Example 13, except that PEG was replaced with polyethylene glycol monomethyl ether.

[0105] Example 18

[0106] The modified polyester was prepared according to the method of Example 15, except that PEG was replaced with polyethylene glycol monomethyl ether.

[0107] Example 19

[0108] The modified polyester was prepared according to the method of Example 9, except that SIPE was replaced with SIPE and 2-hydroxyisobutyric acid in a mass ratio of 1:1.65, and the amount of SIPE and 2-hydroxyisobutyric acid added accounted for 10 wt% of the theoretical polyester yield.

[0109] Example 20

[0110] The modified polyester was prepared according to the method of Example 19, except that the mass ratio of SIPE to 2-hydroxyisobutyric acid was 1:1.5, and the amount of SIPE and 2-hydroxyisobutyric acid added accounted for 10 wt% of the theoretical yield of polyester.

[0111] Example 21

[0112] The modified polyester was prepared according to the method of Example 19, except that the mass ratio of SIPE to 2-hydroxyisobutyric acid was 1:1.8, and the amount of SIPE and 2-hydroxyisobutyric acid added accounted for 10 wt% of the theoretical yield of polyester.

[0113] Example 22

[0114] The modified polyester was prepared according to the method of Example 19, except that the mass ratio of SIPE to 2-hydroxyisobutyric acid was 1:1.2, and the amount of SIPE and 2-hydroxyisobutyric acid added accounted for 10 wt% of the theoretical yield of polyester.

[0115] Example 23

[0116] The modified polyester was prepared according to the method of Example 19, except that the mass ratio of SIPE to 2-hydroxyisobutyric acid was 1:2, and the amount of SIPE and 2-hydroxyisobutyric acid added accounted for 10 wt% of the theoretical yield of polyester.

[0117] Example 24

[0118] The modified polyester was prepared according to the method of Example 19, except that 2-hydroxyisobutyric acid was replaced with 10-hydroxydecanoic acid.

[0119] Example 25

[0120] The modified polyester was prepared according to the method of Example 19, except that SIPE was replaced with sodium isophthalate-5-sulfonate.

[0121] Example 26

[0122] The modified polyester was prepared according to the method of Example 19, except that 2-hydroxyisobutyric acid was replaced with nylon 6.

[0123] Example 27

[0124] The modified polyester was prepared according to the method of Example 19, except that SIPE was replaced with nylon 6.

[0125] Example 28

[0126] The modified polyester was prepared according to the method of Example 19, except that SIPE was replaced with tris(hydroxyethyl) isocyanurate.

[0127] Example 29

[0128] The modified polyester was prepared according to the method of Example 9, except that silicon carbide nanosheets-1 were replaced with silicon carbide nanosheets-2.

[0129] Example 30

[0130] The modified polyester was prepared according to the method of Example 9, except that silicon carbide nanosheets-1 were replaced with silicon carbide nanosheets-3.

[0131] Example 31

[0132] Modified polyester was prepared according to the method of Example 9, except that antimony oxide was replaced with antimony acetate, and the amount of antimony acetate added, calculated as antimony, was 125 ppm of the theoretical yield of polyester.

[0133] Example 32

[0134] Modified polyester was prepared according to the method of Example 9, except that antimony oxide was replaced with antimony glycolate, and the amount of antimony glycolate added, calculated as antimony, accounted for 165 ppm of the theoretical polyester yield.

[0135] Example 33

[0136] The modified polyester was prepared according to the method of Example 9, except that antimony oxide was replaced with tetrabutyl titanate, and the amount of tetrabutyl titanate added, calculated as titanium, accounted for 145 ppm of the theoretical polyester yield.

[0137] Comparative Example 1

[0138] Pure PET polyester was prepared according to the method in Example 1, except that SIPE, silicon carbide nanosheets-1, and PEG were not added after esterification.

[0139] Comparative Example 2

[0140] The modified polyester was prepared according to the method of Example 9, except that silicon carbide nanosheets were not added.

[0141] Comparative Example 3

[0142] The modified polyester was prepared according to the method of Example 9, except that PEG was not added.

[0143] Comparative Example 4

[0144] The modified polyester was prepared according to the method of Example 9, except that SIPE was not added.

[0145] Comparative Example 5

[0146] The modified polyester was prepared according to the method of Example 9, except that silicon carbide nanosheets were replaced with silicon carbide nanospheres.

[0147] Comparative Example 6

[0148] The modified polyester was prepared according to the method of Example 9, except that the amount of PEG added was 0.5 wt% of the theoretical polyester yield.

[0149] Comparative Example 7

[0150] The modified polyester was prepared according to the method of Example 9, except that the amount of PEG added was 20 wt% of the theoretical polyester yield.

[0151] Comparative Example 8

[0152] The modified polyester was prepared according to the method of Example 9, except that the amount of silicon carbide nanosheets added accounted for 0.12 wt% of the theoretical yield of polyester.

[0153] Comparative Example 9

[0154] The modified polyester was prepared according to the method of Example 9, except that the amount of silicon carbide nanosheets added accounted for 2 wt% of the theoretical yield of polyester.

[0155] Comparative Example 10

[0156] The modified polyester was prepared according to the method of Example 28, except that tris(hydroxyethyl) isocyanurate was replaced with triphenyltricarboxylic acid.

[0157] Comparative Example 11

[0158] The modified polyester was prepared according to the method of Example 28, except that tris(hydroxyethyl) isocyanurate was replaced with glycerol.

[0159] The parameters of the modified polyesters obtained in the examples and comparative examples are shown in Table 1.

[0160] Table 1

[0161]

[0162] As can be seen from the results in Table 1, the surface resistivity of the embodiments is lower than that of Comparative Examples 1, 4, and 10-11, and the tensile strength is higher than that of Comparative Examples 2, 3, and 5-9. This indicates that the polyester provided by the present invention can simultaneously possess high antistatic properties and tensile properties, as well as a high thermal conductivity.

[0163] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A modified polyester, characterized in that, The modified polyester contains silicon carbide nanosheets and a copolyester, wherein the copolyester contains structural unit A formed by a modified monomer and structural unit B having an ether group, wherein the modified monomer is selected from at least one of modified monomer a with the structure shown in formula (I), modified monomer b with the structure shown in formula (II), modified monomer c with the structure shown in formula (III), modified monomer d with the structure shown in formula (IV), and modified monomer e with the structure shown in formula (V), wherein the content of the silicon carbide nanosheets in the modified polyester is 0.25-1 wt%, and the content of the structural unit B is 0.1-15 wt%. Among them, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen or C1-C3 alkyl, R7 and R8 are independently hydrogen- or hydroxyl-substituted alkyl groups, R9, R 10 and R 11 Each is independently a C1-C4 alkylene group, R 12 R1, R2 and R3 are each independently C4-C10 alkylene groups, and p and q are each independently natural numbers from 3 to 300.

2. The modified polyester according to claim 1, characterized in that, R7 and R8 are each independently hydroxylated C1-C4 alkyl groups, preferably hydroxylated C2-C3 alkyl groups; Preferably, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen, R9, R 10 and R 11 Each is independently a C2-C3 alkylene group; Preferably, R9, R 10 and R 11 same.

3. The modified polyester according to claim 2, characterized in that, The modified monomer is selected from at least one of modified monomer a, modified monomer c, modified monomer d and modified monomer e; Preferably, the modified monomer is modified monomer a and modified monomer e; Preferably, the mass ratio of the modified monomer a to the modified monomer e is 1:1.5-1.

8.

4. The modified polyester according to any one of claims 1 to 3, characterized in that, The structure of structural unit B is shown in equation (VI) or equation (VII). Among them, R 15 and R 16 Each is independently a C1-C4 alkylene group, R 17 It is a C1-C4 alkyl group, and m and n are each independent natural numbers between 9 and 140, preferably natural numbers between 20 and 50; Preferably, the structure of the structural unit B is as shown in formula (VI).

5. The modified polyester according to any one of claims 1 to 3, characterized in that, In the modified polyester, the content of structural unit A is 10-30 wt%. Preferably, the mass ratio of the silicon carbide nanosheets, the structural unit A, and the structural unit B is 1:10-40:1-12; Preferably, the mass ratio of structural unit A to structural unit B is 1:0.1-1.

5.

6. The modified polyester according to any one of claims 1 to 3, characterized in that, The modified polyester also contains structural unit C as shown in formula (VIII) and structural unit D as shown in formula (IX). Among them, R A It is a C1-C4 alkyl group, R B It is a C2-C4 alkylene group, and p is a natural number between 0 and 4; Preferably, the modified polyester further contains antimony. Preferably, the antimony content in the modified polyester is 125-165 ppm.

7. The modified polyester according to any one of claims 1 to 3, characterized in that, The surface resistivity of the modified polyester is 6 × 10⁻⁶. 8 -2×10 12 Ω, tensile strength of 40-60 MPa, thermal conductivity of 0.17-0.28 W·m -1 ·K -1 ; Preferably, the viscosity of the modified polyester is 0.6-0.7 dL / g.

8. A method for preparing a modified polyester, characterized in that, The preparation method includes the following steps: S1. Under the conditions of esterification reaction, the diacid monomer, diol monomer, modified monomer and catalyst are subjected to the first stage reaction to obtain the prepolymer. S2. Under the conditions of polymerization reaction, the prepolymer, silicon carbide nanosheets and the compound containing ether groups are subjected to a second-stage reaction; The modified monomer is selected from at least one of modified monomer a with the structure shown in formula (I), modified monomer b with the structure shown in formula (II), modified monomer c with the structure shown in formula (III), modified monomer d with the structure shown in formula (IV), and modified monomer e with the structure shown in formula (V). The amount of silicon carbide nanosheets is 0.25-1 wt% based on the theoretical yield of the modified polyester, and the amount of the compound containing the ether group is 0.1-15 wt%. Among them, R4, R5, R6, R 13 R 14 and R 15 Each is independently hydrogen or C1-C3 alkyl, R7 and R8 are independently hydrogen- or hydroxyl-substituted alkyl groups, R9, R 10 and R 11 Each is independently a C1-C4 alkylene group, R 12 R1, R2 and R3 are each independently C4-C10 alkylene groups, and p and q are each independently natural numbers from 3 to 300.

9. The preparation method according to claim 8, characterized in that, Based on the theoretical yield of the modified polyester, the amount of the modified monomer used is 10-30 wt%. Preferably, the ether-containing compound has a structure as shown in formula (VI) or formula (VII). Among them, R 15 and R 16 Each is independently a C1-C4 alkylene group, R 17 It is a C1-C4 alkyl group, and m and n are each independent natural numbers between 9 and 140, preferably natural numbers between 20 and 50; Preferably, the ether-containing compound has a structure as shown in formula (VI); The silicon carbide nanosheets have a length of 0.5-1.3 μm and a width of 1-6 nm. Preferably, the dicarboxylic acid monomer has the structure shown in formula (VIII), and the diol monomer has the structure shown in formula (IX). Among them, R A It is a C1-C4 alkyl group, R B It is a C2-C4 alkylene group, and p is a natural number between 0 and 4; Preferably, the catalyst is an antimony-based catalyst; Preferably, the amount of the antimony-based catalyst, calculated as antimony, is 125-165 ppm based on the theoretical yield of the modified polyester.

10. The use of the modified polyester according to any one of claims 1 to 9 in packaging, textile or electronic materials.